Sepsis: frontiers in diagnosis, resuscitation and antibiotic therapy - Perner,A; Gordon,AC; De,Backer D; Dimopoulos,G; Russell,JA; Lipman,J; Jensen,JU; Singer,M; Bellomo,R; Walsh,T (Intensive Care Medicine, 2016)
Sepsis is a major growing global burden and a major challenge to intensive care clinicians, researchers, guideline committee members and policy makers, because of its high and increasing incidence and great pathophysiological, molecular, genetic and clinical complexity. In spite of recent progress, short-term mortality remains high and there is growing evidence of long-term morbidity and increased long-term mortality in survivors of sepsis both in developed and developing countries. Further improvement in the care of patients with sepsis will impact upon global health. In this narrative review, invited experts describe the expected challenges and progress to be made in the near future. We focus on diagnosis, resuscitation (fluids, vasopressors, inotropes, blood transfusion and hemodynamic targets) and infection (antibiotics and infection biomarkers), as these areas are key, if initial management and subsequent outcomes are to be improved in patients with sepsis.